Enterovirus A71 2B Inhibits Interferon-Activated JAK/STAT Signaling by Inducing Caspase-3-Dependent Karyopherin-α1 Degradation - Sun, Menghuai; Lin, Qian; Wang, Chunyang; Xing, Jiao; Yan, Kunlong; Liu, Zhifeng; Jin, Yu; Cardona, Carol J.; Xing, Zheng (Frontiers in Microbiology, 2021)
Enterovirus A71 (EV-A71) is a major pathogen that causes the hand, foot, and mouth disease, which could be fatal with neurological complications in children. The underlying mechanism for the severe pathogenicity remains obscure, but impaired or aberrant innate immunity is considered to play a key role in viral pathogenesis. We reported previously that EV-A71 suppressed type I interferon (IFN) responses by inducing degradation of karyopherin-α1 (KPNA1), a component of the p-STAT1/2 complex. In this report, we showed that 2B, a nonstructural protein of EV-A71, was critical to the suppression of the IFN-α-induced type I response in infected cells. Among viral proteins, 2B was the only one that was involved in the degradation of KPNA1, which impeded the formation of the p-STAT1/2/KPNA1 complex and blocked the translocation of p-STAT1/2 into the nucleus upon IFN-α stimulation. Degradation of KPNA1 induced by 2B can be inhibited in the cells pre-treated with Z-DEVD-FMK, a caspase-3 inhibitor, or siRNA targeting caspase-3, indicating that 2B-induced degradation of KPNA1 was caspase-3 dependent. The mechanism by which 2B functioned in the dysregulation of the IFN signaling was analyzed and a putative hydrophilic domain (H1) in the N-terminus of 2B was characterized to be critical for the release of cytochrome c into the cytosol for the activation of pro-caspase-3. We generated an EV-A71 infectious clone (rD1), which was deficient of the H1 domain. In rD1-infected cells, degradation of KPNA1 was relieved and the infected cells were more sensitive to IFN-α, leading to decreased viral replication, in comparison to the cells infected with the virus carrying a full length B2. Our findings demonstrated that EV-A71 2B protein plays an important role in dysregulating JAK-STAT signaling through its involvement in promoting caspase-3 dependent degradation of KPNA1, which represents a novel strategy employed by EV-A71 to evade host antiviral innate immunity.